Baseline-Dependent Biological Response to Peri-Implant Soft Tissue Augmentation: A Secondary Analysis of a Randomized Clinical Trial - Jakub Hadzik; Paweł Kubasiewicz-Ross; Umberto Romeo; Krzysztof Kujawa; Nicola Alberto Valente; Marzena Dominiak (Journal of Functional Biomaterials, 2026)
Objectives: Clinical outcomes of peri-implant soft tissue augmentation remain variable, and baseline-associated factors of treatment response are poorly understood. This exploratory study aimed to evaluate baseline-associated patterns of peri-implant soft tissue gain following augmentation with connective tissue grafts (CTG) and volume-stable collagen matrices (VCMX). Materials and Methods: This study represents a secondary analysis of a randomized clinical trial including 32 implant sites (CTG, n = 16; VCMX, n = 16). Peri-implant soft tissue thickness (STT) was measured using high-frequency ultrasonography at baseline (T0), 3 months (T1), and 12 months (T2). Absolute and relative STT gains were analyzed, and their relationship with baseline thickness was assessed. Results: Both augmentation approaches resulted in significant increases in soft tissue thickness, with most of the gain occurring during the early healing phase. At 12 months, CTG demonstrated greater absolute tissue gain than VCMX. At the mid-buccal measurement site, mean relative gain was approximately 225% with CTG and 147% with VCMX. The strongest inverse correlation between baseline STT and relative gain was also observed at this site in the CTG group (r = −0.815, p < 0.001). Sites with thinner tissues showed greater proportional increases, whereas thicker tissues demonstrated a reduced relative response. Conclusions: Relative soft tissue gain was inversely associated with baseline soft tissue thickness. Thinner tissues exhibit greater proportional increases, whereas thicker tissues demonstrate a lower relative gain. These findings support a phenotype-informed and individualized approach to peri-implant soft tissue management.